Analisa Peluang Dan Ancaman Perdagangan Bebas Sektor Perkebunan (Indonesia-Malaysia-Vietnam) - Mita Nur Meilani; Dela Fitriana; Lia Ardipa; M. Agung Abdullah Zidan; Daspar (Jurnal Ekonomi dan Bisnis Digital, 2024)
International trade between Indonesia, Malaysia and vietnam has a strong and important relationship in the economies of both countries. The two countries share the types of goods traded, including palm oil, rubber, electronics, plantations and other agricultural products. Trade policies, such as free trade agreements and economic partnerships, also influence trade flows between the two. The aim of this research is to determine economic cooperation between Indonesia and Malaysia, especially in the tea plantation sector. This research uses a literacy method, namely a method where data is obtained from journals, books and other sources on the internet. It is hoped that the results of this research will provide new knowledge to readers so that it will have a positive impact on the progress of international trade.